Systematic Literature Review: Utilization of Video Media in Math Learning - Muhammad Ainuddin Daahiljabir; Masrukan; Iqbal Kharisudin (Hipotenusa: Journal of Mathematical Society, 2023)
Learning media plays an important role for teachers in carrying out learning activities in the classroom. Video-based learning media is one of the learning media that makes students able to understand the material presented by the teacher, because videos can show more real objects. Video-based learning media is also widely used by teachers because it has a good and successful influence on mathematics learning activities in the classroom. Making learning video media can use several applications such as powerpoint, videoscribe, canva, vegaspro, geogebra, powtoon, and others. The purpose of this study was to determine that video-based mathematics learning media has a positive effect on mathematics learning. This research is looking for several articles related to the use of video media in learning mathematics. The method used in this research is SLR (Systematic Literature Review). SLR is a technique of systematically collecting data, critically testing data, and collecting results that are in accordance with the topics used in the study. Research results from several accredited international and national journals show that the use of media in the form of learning videos in mathematics learning can help teachers and students in carrying out mathematics learning activities.